La Vierge Marie et ses images chez Gautier de Coinci et Césaire de Heisterbach - Sansterre, Jean-Marie (Viator (English and Multilingual Edition), 2010)
Abstract Based on the complete reading of the Miracles de Nostre Dame (between 1214–1233), the first part of the article highlights the importance of images of the Virgin in personal piety and pastoral guidance of the Benedictine Gautier of Coinci. They appear inherent to Christianity and it is necessary to venerate them for saving the intercession of Mary. The study shows also how the author, but never formally, declines in various ways the relationship between image and prototype by the miracles that adapts and the messages he wants to convey. The second part explores the miraculous Marian stories of two collections strictly contemporary that of Gautier, the Dialogus Miraculorum and the Libri Miraculorum (I and II) of Cesaire of Heisterbach. It includes much attention to images of the Virgin, but with inflections due mainly to the different nature of the collections, to the choice to focus on contemporary miracles and to the membership of Cesaire to the Cistercian order. On the other hand, assertions of Gautier and Cesaire prove that, nor the clergy, the laity did not form a homogeneous group in their attitudes and beliefs relating to images and their miracles.